Updating the Phylodynamics of Yellow Fever Virus 2016–2019 Brazilian Outbreak With New 2018 and 2019 São Paulo Genomes - Moreira Salles, Ana Paula; de Seixas Santos Nastri, Ana Catharina; Ho, Yeh-Li; Vilas Boas Casadio, Luciana; Emanuel Amgarten, Deyvid; Justo Arévalo, Santiago; Soares Gomes-Gouvea, Michele; Jose Carrilho, Flair; de Mello Malta, Fernanda; Rebello Pinho, João Renato (Frontiers in Microbiology, 2022)
The recent outbreak of yellow fever (YF) in São Paulo during 2016–2019 has been one of the most severe in the last decades, spreading to areas with low vaccine coverage. The aim of this study was to assess the genetic diversity of the yellow fever virus (YFV) from São Paulo 2016–2019 outbreak, integrating the available genomic data with new genomes from patients from the Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo (HCFMUSP). Using phylodynamics, we proposed the existence of new IE subclades, described their sequence signatures, and determined their locations and time of origin. Plasma or urine samples from acute severe YF cases (n = 56) with polymerase chain reaction (PCR) positive to YFV were submitted to viral genome amplification using 12 sets of primers. Thirty-nine amplified genomes were subsequently sequenced using next-generation sequencing (NGS). These 39 sequences, together with all the complete genomes publicly available, were aligned and used to determine nucleotide/amino acids substitutions and perform phylogenetic and phylodynamic analysis. All YFV genomes generated in this study belonged to the genotype South American I subgroup E. Twenty-one non-synonymous substitutions were identified among the new generated genomes. We analyzed two major clades of the genotypes IE, IE1, and IE2 and proposed the existence of subclades based on their sequence signatures. Also, we described the location and time of origin of these subclades. Overall, our findings provide an overview of YFV genomic characterization and phylodynamics of the 2016–2019 outbreak contributing to future virological and epidemiological studies.